ROLE OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN THE DEVELOPMENT OF CHHATTISGARH - Nayak, Manoj Kumar; Soni, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
MSMEs, or micro, small, and medium-sized enterprises, have been named the "growth engine" for all emerging nations, including India. MSMEs have contributed significantly to the general economic development of states like Chhattisgarh, where thousands of people are unemployed or underemployed and confront poverty-related difficulties. MSMEs, one of the largest employers in the state after agriculture, offer instant large-scale employment with low-cost investments and play an important role in the state economy. Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in driving economic development, fostering entrepreneurship, and promoting inclusive growth across India. As engines of innovation and employment, MSMEs contribute significantly to the country’s GDP, exports, and industrial output. In the context of Chhattisgarh—a resource-rich, yet economically diverse state—MSMEs have emerged as a crucial force in transforming the rural and semi-urban economy, bridging income disparities, and creating sustainable livelihoods. Chhattisgarh's strategic location, availability of natural resources, and policy incentives have facilitated the growth of a variety of MSME clusters in sectors such as agro-processing, textiles, engineering, and handicrafts. These enterprises not only support large-scale industries by forming part of the supply chain but also encourage local entrepreneurship and skill development. Despite their contribution, the sector continues to face challenges related to infrastructure, access to finance, market linkages, and regulatory hurdles. This research paper aims to explore the role of MSMEs in the socio-economic development of Chhattisgarh, assessing their contribution to employment generation, regional development, and investment attraction. The study also seeks to identify key obstacles that hinder their growth and to propose policy recommendations for strengthening the MSME ecosystem in the state. The purpose of this research is to look at the growth and development of MSMEs in Chhattisgarh. The primary purpose of the research is to examine the employment opportunities provided by small scale units in the state’s designated study zone. The majority of the information was gathered via a postal questionnaire and personal observation. According to the conclusions of this study, MSMEs are critical to Chhattisgarh’s economic development. Using Microsoft Excel, the data was qualitatively analysed and presented in the form of tables and figures.